Gods, graves and graphs – social and semantic network analysis based on Ancient Egyptian and Indian corpora - Frederik Elwert; Simone Gerhards; Sven Sellmer (Digital Classics Online, 2017)
In this paper, the authors show the application and use of automated text network analysis based on ancient corpora. The examples draw from Ancient Egyptian sources and the Indian Mahābhārata. Different text-based network generation algorithms like “Nubbi” or “Textplot” are presented in order to showcase alternative methodological approaches. Visualizations of the generated networks will help scholars to grasp complex social and semantic text structures and serve as a starting point for new research questions. All tools for applying the methods to ancient corpora are available as open source software.